The Influence of Asset and Liability Management on Dividend Policy and Firm Value of Listed Banking Companies in the Indonesia Stock Exchange - Yudih, Sudirman; Mustamin, Asyraf (Jurnal Ilmiah Akuntansi Peradaban, 2024)
This study aims to examine the effect of asset and liability management on dividend policy and Firm value of listed banking companies in the Indonesia Stock Exchange. This study used panel data from banking statistics reports and annual IDX statistics. This research used Structural Equation Model as the data analysis. The results of the study found that, asset management has a positive and significant effect on dividend policy and firm value. Meanwhile, liability management has a negative and insignificant effect on dividend policy. and company value.